Changes in TFG gene expression in bovine leucocytes transformed by Theileria annulata - Zhao, Hong-xi; Li, Xia; Liu, Jun-long; Guan, Gui-quan; Luo, Jian-xun (Frontiers in Veterinary Science, 2022)
Theileria annulata schizont-infected host cells in culture in vitro show unlimited proliferation similar to tumor cells; thus far, T. annulata and T. parva are the only eukaryotes that have been found to transform mammalian cells (immortalized). The transformation of these cells is reversible; when the parasite is eliminated in transformed cells by buparvaquone (BW720c), the host cells show normal growth and apoptosis. TFG is a tropomyosin-receptor kinase fused gene that is conserved among many species and is an important proto-oncogene. In this study, the bovine TFG gene was amplified by PCR from the cDNA of T. annulata schizont-transformed cells, cloned into the pGEX-4T-1 vector and expressed in Escherichia coli BL21 (DE3). After purification, the fusion protein was injected into rabbits to produce polyclonal antibodies. Using T. annulata-transformed cells together with BW720c treatment to kill the parasite, we aimed to identify changes in TFG gene expression by real-time PCR and Western blotting. The results showed that the bovine TFG gene was 582 bp in size; SDS-PAGE analysis showed that the fusion protein was expressed in BL21 (DE3) cells with a molecular mass of 48 kD, and Western blotting indicated that the polyclonal antibodies could react with bovine TFG proteins from T. annulata-transformed cells and showed high specificity. Compared with that in the control group, the transcription level of the host TFG gene decreased significantly in the BW720c test group, and the expression of host tumor-related TFG protein decreased sharply after 72 h of drug treatment, suggesting that the TFG protein expression in transformed cells was directly related to T. annulata. This finding laid a foundation for further study on the interaction between T. annulata and host cells.